2009
DOI: 10.1002/ijc.24255
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic function of ezrin in human metastatic melanomas

Abstract: The membrane cytoskeleton cross-linker, ezrin, has recently been depicted as a key regulator in the progression and metastasis of several pediatric tumors. Less defined appears the role of ezrin in human adult tumors, especially melanoma. We therefore addressed ezrin involvement in the metastatic phenotype of human adult metastatic melanoma cells. Our results show that cells resected from melanoma metastatic lesions of patients, display marked metastatic spreading capacity in SCID mice organs. Stable transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 54 publications
4
58
0
Order By: Relevance
“…Previous studies have reveal that the level of Ezrin expression is positively related to the degree of malignancy in many tumors (Ilmonen et al, 2005;Li et al, 2008;Federici et al, 2009). And over expression of Ezrin usually correlates with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reveal that the level of Ezrin expression is positively related to the degree of malignancy in many tumors (Ilmonen et al, 2005;Li et al, 2008;Federici et al, 2009). And over expression of Ezrin usually correlates with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…But aberrant expression of Ezrin, especially over expression, has been found associated closely with malignant tumors (Bruce et al, 2007). Ezrin was over expression in melanoma and the level of expression was parallel with its thickness and invasive ability (Ilmonen et al, 2005;Federici et al, 2009). And there is a positive correlation between Ezrin overexpression and the metastatic potential of human breast cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Ezrin is also reported to interact with podoplanin, a small membrane mucin induced in oral squamous cell carcinomas, which colocalizes with ezrin [40] and induces an epithelial-mesenchymal transition in an ezrindependent manner [41]. Finally, we can mention that molecular interactions with ezrin were shown to allow membrane localization of Lamp-1 (also known as CD107a) [30], a heavily glycosylated transmembrane protein, involved in adhesion of cancer cells to the extracellular matrix. This membrane localization correlated with a high metastatic potential.…”
Section: Erms In Pathological Processesmentioning
confidence: 87%
“…Clinical studies have shown that ezrin overexpression also correlated with adult tumor metastasis. Ezrin overexpression increased migration of metastatic melanoma [30], pancreatic cancer cells [31], or hepatocellular carcinoma [32]. Conversely, ezrin silencing or inhibition contributed to decreased cell motility [33][34][35][36].…”
Section: Erms In Pathological Processesmentioning
confidence: 99%
“…Ezrin is also of interest from a cancer perspective, with an established role in metastasis (Brambilla and Fais, 2009;Fais, 2004;Federici et al, 2009;Zhou et al, 2010a) and an emerging role in proliferative signalling (Gautreau et al, 1999;Heiska et al, 2011;Kishore et al, 2005;Srivastava et al, 2005). Ezrin has been previously shown to be increased in leukaemic cells (Monni et al, 2008) and has been identified as a target of oncogenic signalling from extracellular signalling mediators PDGF, EGF and HGF as well as intracellular oncogenic kinases Src, Lck and Rho (Crepaldi et al, 1997;Fazioli et al, 1993;Monni et al, 2008).…”
Section: Discussionmentioning
confidence: 99%